2010
DOI: 10.2754/avb201079020203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Trace Elements on the Growth Performance and Their Distribution in the Breast and Thigh Muscles Depending on the Age of Broiler Chickens

Abstract: This study was designed to determine the effects of dietary supplementation of different doses and forms of Cu, Zn, Fe, Mn and Se on the growth performance and concentration of these elements in the breast and thigh muscle of Ross 308 broiler chickens at the age of 21, 35 and 42 days. The diets for groups 1 and 2 of birds were supplemented with equivalent amounts of trace elements in an inorganic form (Cu sulphate 5 mg·kg , respectively. Groups 3 and 4 received the same feed as chickens in groups 1 and 2 but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
4
24
0
2
Order By: Relevance
“…These changes could have a close relation to the higher amount of Cu and Mn in the breast and thigh muscles on day 21 of life compared to the birds aged 42 days that were included in the same study (Petrovič et al 2010). All these changes can reflect a notable development of parenchymatous organs and the bones of broilers as well as higher efficiency of lipid metabolism in the first 3 weeks of their life.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…These changes could have a close relation to the higher amount of Cu and Mn in the breast and thigh muscles on day 21 of life compared to the birds aged 42 days that were included in the same study (Petrovič et al 2010). All these changes can reflect a notable development of parenchymatous organs and the bones of broilers as well as higher efficiency of lipid metabolism in the first 3 weeks of their life.…”
Section: Resultsmentioning
confidence: 79%
“…In addition, Petrovič et al (2010) found in the same experiment that the concentration of Se in the breast and thigh muscles was significantly increased in groups of broilers fed selenized yeast compared to sodium selenite, and age dependent changes of this index were found in both muscles only between the 1 st vs. 2 nd sampling. Similarly, no significant differences were shown in the form of selenium supplemented and GSH-Px activity in blood of adult poultry (Kuricová et al 1999;Petrovič et al 2006).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations